And they called it Camelot : a novel of Jacqueline Bouvier Kennedy Onassis - Thornton, Stephanie, 1980- (Berkley, 2020)
"An unforgettable portrait of the iconic life of Jackie O as she transforms herself into an American legend from acclaimed author Stephanie Marie Thornton. Millions fell silent, stricken by grief and disillusionment, as news of President Kennedy's assassination streaked across the globe. Where were you when it happened, they asked? But for one woman the answer has always been the same--for every step, every victory, and every defeat--she was right beside him. Born into luxury and beauty, spontaneous young Jacqueline Bouvier aspires to be more than the Debutante of the Year, even if she isn't quite sure what that means. A whirlwind courtship and fairytale wedding to handsome war-hero John F. Kennedy propel her into a startling new world of power and politics. Filled with incredible highs and unimaginable challenges, Jackie learns to hone her survival skills. Her grace and grit help catapult JFK from the Senate to the Oval Office in one of the closest races in U.S. history. Jackie awes the country with her elegance and poise even as she is plagued by self-doubt over whether she can be the wife, mother, and First Lady that her husband and the country need. Then Jackie accompanies JFK to Dallas and their thousand days of magic come to an abrupt and devastating end--forcing Jackie to pick up the ruined fragments of her life and forge a triumphant new identity"--